CEP215 and AURKA regulate spindle pole focusing and aMTOC organization in mouse oocytes. Issue 3 (March 2020) - Wang, Xiaotian; Baumann, Claudia; De La Fuente, Rabindranath; Viveiros, Maria M
Abstract : Acentriolar microtubule-organizing centers (aMTOCs) play a critical role in stable meiotic spindle assembly in oocytes, necessary for accurate chromosome segregation. Yet, there is a limited understanding of the essential regulatory components of these unique MTOCs. In somatic cells, CEP215 (Centrosomal Protein 215) serves as an important regulator of centrosome maturation and spindle organization. Here, we assessed whether it has a similar function in mouse oocytes. CEP215 was detected in oocyte lysates and specifically localized to aMTOCs throughout the progression of meiosis in a pericentrin-dependent manner. Super-resolution microscopy revealed CEP215 co-localization with pericentrin and a unique pore/ring-like structural organization of aMTOCs. Interestingly, inhibition of Aurora Kinase A in either MI or MII-stage oocytes resulted in a striking loss of the ring-like aMTOC organization and pronounced CEP215 clustering at spindle poles, as well as shorter spindles with highly focused poles. In vitro siRNA-mediated transcript knockdown effectively reduced CEP215 in approximately 85% of the oocytes. Maturation rates to MII were similar in the Cep215 siRNA and injected controls; however, a high percentage (~40%) of the Cep215 -knockdown oocytes showed notable variations in spindle pole focusing. Surprisingly, pericentrin and γ-tubulin localization and fluorescence intensity at aMTOCs were unaltered in knockdown oocytes, contrasting with mitotic cells where CEP215 depletion reduced γ-tubulin at centrosomes. Our results demonstrate that CEP215 is a functional component of oocyte aMTOCs and participates in the regulation of meiotic spindle pole focusing. Moreover, these studies reveal a vital role for Aurora Kinase A activity in the maintenance of aMTOC organization in oocytes.